Good Corporate Governance and Liquidity: The Urgency of Risk Disclosure of Manufacturing Companies in Indonesia - Arry Eksandy (Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to determine the influence of the liquidity (those that are proxy ed with current ratio) and good corporate governance (those that are proxied with size of the board of commissioners, proportion of independent commissioners, institutional ownership, and managerial ownership) to risk disclosure. The analytical method used is panel data regression analysis for manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period of 2016-2018. The research sample consisted of 13 companies with a purposive sampling method. The reason for using the 2016-2018 period is to get the condition of manufacturing companies in Indonesia which were still relatively stable before the Covid-19 pandemic. The results showed that managerial ownership had a significant positive effect on risk disclosure. Liquidity, size of the board of commissioners, proportion of independent commissioners, and institutional ownership do not have a significant influence on risk disclosure. The novelty of this research is the formation of a theoretical model of good corporate governance through indicators of managerial ownership in influencing risk disclosure, thereby providing an overview of the importance of ownership by managers so that risk disclosure can be carried out optimally. This research contributes to the understanding of the factors influencing risk disclosure and provides guidance for companies in improving good corporate governance to achieve optimal risk disclosure.